IMMUNOPATHOLOGY AND GENETIC OF ATOPIC DERMATITIS - Bilozorov, O.P. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Clinical investigations have shown that atopic dermatitis is characterized with high concentration of IgE and increased level of circulating immune complexes due to antigenic load, which is partially connected with skin microorganisms. Literature data are reviewed about atopy genetic and localization of genes connected with this pathology.